Devil's excrement or manna from heaven?: A survey of strategies in natural resource wealth management. Issue 1 (7th April 2015) - Mendoza, Ronald U.; MacArthur, Harold J.; Ong Lopez, Anne Beline
Abstract : Purpose: – This paper aims to provide an updated review of policy literature and evidence on the development implications of extractive industries. Design/methodology/approach: – It synthesizes the main lessons drawn from an extensive review of policy and academic literature on this topic. It outlines the risks attached to the natural resource curse as well as the associated solutions, as demonstrated by empirical evidence and policy experience. Findings: – Based on the authors' review of case studies and multi-country empirical analyses, there is a mixed picture on the link between extractive industries and inclusive growth. The authors find that, on the one hand, significant risks are commonly associated with the natural resource curse faced by countries that wish to tap this wealth for development. On the other hand, the mixed results also suggest that the many challenges related to expanding extractive industries are not necessarily unavoidable. Practical implications: – For policymakers, the main message is that some countries that have taken important steps to improve the governance of their wealth as well as channel these toward productive investments – notably human capital – appear to have transformed the natural resource curse into a boon for development. Originality/value: – The main contribution of this paper is that it provides the most comprehensive review to date on this body of the policy and academic literature. It will serve as a guide for policymakers, civil society and other stakeholders working on issues linked to extractive industries.